Pembentukan Organisasi Kelompok Budidaya Lele di Desa Codo Kecamatan Wajak Kabupaten Malang - Tri Prasetyawan; Yuswanti Yuswanti; Retno Palupi (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
Real Work Lectures (KKN) is an implementation of one aspect of the Tri Dharma of Higher Education, namely community service. Through KKN, students have the opportunity to apply the knowledge and skills they have acquired at college in real contexts in society. KKN also aims to develop students' social awareness and responsibility towards society as well as increase their sense of empathy and concern for social, economic and cultural conditions in various regions. Codo Village is one of the villages in the Wajak District, Malang Regency. This village is a partner of the State University of Malang as one of the target villages for the KKN program. Based on the results of observations, one of the potentials found in Codo Village is catfish farming and cultivation. Based on the results of field observations, it is known that the catfish farming organization has not yet been formed, the catfish farming group community in Codo village is still operating at a rudimentary level. Method of implementing activities: (1) observation; (2) data collection on catfish cultivation groups; (3) formation of organizations; (4) explain the job description and functions of each member; (5) training in making proposals for the formation of a catfish cultivation group organization in Codo village. The results of the implementation of the program/activity for the formation of a catfish cultivation group organization in Codo village, Wajak subdistrict, Malang Regency are very satisfying because 87% of the expected results have been achieved.